INFLUENCE OF HARVESTING AND DRYING TECHNIQUES ON MICROFLORA AND MYCOTOXIN CONTAMINATION OF FIGS - OZAY, G; ARAN, N; PALA, M (VCH PUBLISHERS INC, 1995)
Mould growth and mycotoxin (aflatoxins and ochratoxin A) formation were examined in the 1993 dried figs crop. The relationships between mould/mycotoxin contamination and orchard conditions, different harvesting techniques, harvesting time and intactness of fruits were investigated. The fruits were examined during drying and effects of different pretreatments, sun drying and solar drying on the mould and mycotoxin contamination in figs were also studied. Aflatoxins (B-1, B-2, G(1) and G(2)) were not present in the firm or shrivelled ripe figs. Among the samples examined during drying, only one of the 32 samples was found to be aflatoxin positive. Ochratoxin A was not detected in any of the samples analysed. The moisture content, a(w) and pH values of full ripe and shrivelled fruits were suitable for mould growth and mycotoxin formation while these parameters in pretreated and dried fruits were found to be too low to allow such outcome. It was observed that harvesting the fruit by hand-treating with different solutions and application of solar drying were effective in reducing contamination level.
Keywords: Food Science & Technology